2001
DOI: 10.1152/ajplung.2001.280.2.l363
|View full text |Cite
|
Sign up to set email alerts
|

IL-10 gene knockout attenuates allergen-induced airway hyperresponsiveness in C57BL/6 mice

Abstract: Intratracheal administration of interleukin-10 (IL-10) has been reported to inhibit allergic inflammation but augment airway hyperresponsiveness (AHR). In the present study, airway and smooth muscle responsiveness to methacholine (MCh) were compared in wild-type (WT) and IL-10-deficient (IL-10-KO) mice to investigate the role of endogenous IL-10 in AHR development. Naive WT and IL-10-KO mice exhibited similar dose-dependent increases in airway resistance (Raw) to intravenous MCh. Sensitization and challenge wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
64
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 27 publications
9
64
2
Order By: Relevance
“…Although our AR and inflammation responses generally agree with those of prior studies (30,31,34), they are not consistent with one study in which IL-10 Ϫ/Ϫ mice demonstrated significantly decreased BAL macrophage counts and increased eosinophilia and AR, as compared with the C57 mice (41). Those responses were consistent with what would be expected with a lack of IL-10 as an anti-inflammatory cytokine and are in agreement with phenotypic expectations that would come from human data demonstrating a lack of IL-10 production in asthmatics (7,8).…”
Section: Critique Of Methodssupporting
confidence: 92%
See 4 more Smart Citations
“…Although our AR and inflammation responses generally agree with those of prior studies (30,31,34), they are not consistent with one study in which IL-10 Ϫ/Ϫ mice demonstrated significantly decreased BAL macrophage counts and increased eosinophilia and AR, as compared with the C57 mice (41). Those responses were consistent with what would be expected with a lack of IL-10 as an anti-inflammatory cytokine and are in agreement with phenotypic expectations that would come from human data demonstrating a lack of IL-10 production in asthmatics (7,8).…”
Section: Critique Of Methodssupporting
confidence: 92%
“…This trend was consistent with an AR increase reported previously (30,31); however, its magnitude was small, perhaps due to the mild nature of our inflammatory challenge. Administration of L-NIL resulted in a significant increase in AR in the absence of IL-10 that was not different from the C57 IL-10-sufficient case.…”
Section: Airway Il-4 Nitrite and Reactivitysupporting
confidence: 93%
See 3 more Smart Citations